Trophic positioning among native and non-indigenous species in the eastern Mediterranean Sea - TÜZÜN, SUNA; GÜCÜ, ALI CEMAL (Mediterranean Marine Science, 2024)
The substantial influx of non-indigenous species (NIS) into the eastern Mediterranean Sea from the Suez Canal has prompted questions about the mechanisms enabling their establishment and the resulting impacts on native species. We focus on the trophic level dynamics of the dominant native red mullet (Mullus barbatus) and the four NIS Pomadasys stridens, Upeneus moluccensis, U. pori, and Parupeneus forsskali. Using various methods, including trophic level estimations, intestine length analysis, and monthly trophic level variations, we assessed their trophic positions and flexibility. The results indicate that compared to M. barbatus, P. stridens occupies a lower trophic level due to its omnivorous nature, potentially facilitating its biomass increase. This lower trophic position is further supported by its lengthy intestine relative to size. Conversely, U. moluccensis, U. pori, and P. forsskali position themselves consistently at higher trophic levels than M. barbatus. Monthly trophic level variations suggest temporal dietary changes, which point to seasonal impacts on NIS success. M. barbatus’s resilience, including its preference for polychaetes, may explain its sustained dominance amid competition. This study sheds light on NIS-native species coexistence, further suggesting that NIS success could stem from exploitation of vacant niches and adaptation to new food sources.